On the strong convergence of weighted sums of widely dependent random variables. Issue 21 (1st November 2016) - Cheng, Dongya; Zhang, Wenhai; Wang, Yuebao
ABSTRACT: For widely dependent random variables, we present some results on the strong convergence of weighted sums, including results on almost surely (a.s.) and complete convergence. To this end, we verified some Borel–Cantelli lemmas of the widely dependent random variables. The above-mentioned random variables contain common negatively dependent random variables, some positively dependent random variables, and some others; therefore, the obtained results extend and improve some existing results.